Is the whole greater than the sum of its parts? A management project to research Procurement in the NHS: why the national strategies to centralise contracting and standardise the products and services the NHS buys have not been adopted - Williams, John (2022)
This management project explores why the national strategies to centralise contracting and standardise the products and services the NHS buys have not been adopted. It investigates why change has not happened, reviewing previously commissioned reports into NHS Procurement and researching relevant change theory. The primary research focuses on the reasons for a lack of change in more detail, and investigates how the two current NHS England national initiatives that were launched following the Carter Report into Reduced Variation and Operational Productivity (Lord Carter of Coles, 2016), are faring. The primary research involved one to one qualitative interviews with 8 Procurement leaders across the NHS, followed by a survey which had 86 responses representing a 7% response rate, and finally a focus group made up of a cross section of 6 participants from one local Trust Procurement team. The research finds that although the vision of a more centralised and category specific specialised approach is widely supported by procurement teams, three main factors are preventing this change from being implemented. These are: poor communications, a lack of resources, and national initiatives not being a local Trust priority. The management project offers recommendations for future success by looking at relevant academic literature and best practice, proposing solutions based on the outputs of the primary research and using Kotter’s eight step model (Kotter, 1996) as a framework for how this change could be delivered.